2017
DOI: 10.1159/000481350
|View full text |Cite
|
Sign up to set email alerts
|

Psychoacoustics and Neurophysiological Alterations after 30-36 Hours of Sleep Deprivation

Abstract: Background and Aim: Sleep deprivation (SD) may result in perceptual and cognitive alterations in healthy subjects. Our objective was to compare whether psychoacoustics and neurophysiological variables in healthy subjects were altered after SD of 30-36 h. Method: We examined 22 subjects by means of several psychoacoustics tests, P300 and mismatch negativity (MMN) recordings, and brainstem auditory evoked potentials (BAEP) before and after 30-36 h of SD. Results: In the psychoacoustics tests, we found that after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Studies have shown that sleep deprivation can affect human cognition and overall brain performance [1]. The effects of sleep deprivation are not just confined to brain function; in fact, it can affect other human organ systems as well [2-4].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that sleep deprivation can affect human cognition and overall brain performance [1]. The effects of sleep deprivation are not just confined to brain function; in fact, it can affect other human organ systems as well [2-4].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, those with early dementia may present with low mood, apathy and insomnia [ 31 ], but loss of interest and sleep disorders are also signs of depression [ 68 , 69 ]. In addition, depression can be related to poor sleep quality [ 70 ], which can also affect cognition [ 71 ]. Therefore, whilst these symptoms may be indicative of dementia, primary care physicians should be aware that the relationship is complex and be careful not to misdiagnose people.…”
Section: Discussionmentioning
confidence: 99%